Endoscopic Fluorescence‐Guided Surgery for Sinonasal Cancer Using an Antibody‐Dye Conjugate. (19th December 2019) - Hart, Zachary P.; Nishio, Naoki; Krishnan, Giri; Lu, Guolan; Zhou, Quan; Fakurnejad, Shayan; Wormald, Peter John; van den Berg, Nynke S.; Rosenthal, Eben L.; Baik, Fred M.
Abstract : Objective: Endoscopic resection of sinonasal squamous cell carcinoma has become the standard of care, but challenges remain in obtaining clear resection margins. The current study evaluated the feasibility of endoscopic fluorescence‐guided surgery (FGS) to improve surgical resection in a human sinus surgical model. Methods: A fluorescence endoscope optimized for near‐infrared (NIR) fluorescence detection was evaluated in a phantom study. Various endoscope diameters (4 and 10 mm) and viewing angles (0, 30, and 45 degrees) were evaluated to determine the sensitivity of the system for IRDye800CW detection at various working distances (1–5 cm). Endoscopic FGS was then validated in a three‐dimensional human sinus surgical model to which squamous cell tumors derived from mice were inserted. Mice had received intravenous panitumumab‐IRDye800CW and upon fluorescence‐guided tumor resection, mean fluorescence intensity (MFI) and tumor‐to‐background ratio (TBR) were calculated in in situ and ex vivo settings. Results: A significantly higher fluorescence intensity was found when using the 10‐mm diameter endoscope compared to the 4mm diameter endoscope ( P  < .001). No significant difference in MFI was found among the viewing angles of the 4‐mm diameter endoscope. Using the human sinus model, the highest MFI and TBR were obtained at a 1‐cm working distance compared to longer working distances. Conclusion: We demonstrate that clinically acceptable TBRs were obtained with several working distances to discriminate tumor tissue from adjacent normal tissue in a human sinus model, and that endoscopic FGS may have great potential in identifying residual tumor tissue regions during surgery. Laryngoscope, 2019